منهج مادة اللغة العربية في المدارس الثانوية بآتشيه إندونيسيا - Alfiddhah binti Muhammad Yunus (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2009)
This research is to evaluate the curriculum of Arabic subject in secondary schools, in Aceh – Indonesia. The study aims to indentify the weakness of students in learning Arabic language and to suggest and recommend those schools about the Arabic subject curriculum used for improvement. The researcher is designed to conduct interviews with the school headmaster, teachers, and group of students because the curriculum of Arabic subject in selected Aceh schools needs to be evaluated, in order to suit the objectives of the schools and their students. This study found that some teachers were not qualified in teaching Arabic language because of the lack of training. The finding expects to solve the problems by providing a picture of problems faced by teacher and students in Aceh. It also provides suggestion in order to improve teaching ability of the Arabic subject teachers and students in secondary schools in Aceh Indonesia.